Biochemical Markers Of Oxidative Stress In Mugil Cephalus Exposed To Cadmium, Copper, Lead And Zinc - J.S.I RAJKUMAR; M.C JOHN MILTON (International Journal of Pharma and Bio Sciences, 2011)
Oxidative damage and antioxidant properties were studied in Mugil cephalus exposed to cadmium, copper, lead and zinc in chronic toxicity test as pollution biomarkers. The elevated thiobarbituric acid reactive substances (TBA-RS) levels observed under exposure to heavy metals, leading to the oxidative damage resulting in lipid peroxidation (LPX). Increased activities of antioxidants, catalase (CAT) and glutathione-S-transferase (GST) under long term exposures to heavy metals are more prominent to metal stress suggesting activation of physiological mechanism to scavenge the ROS produced. Decreased values of reduced glutathione (GSH) on long exposures to cadmium and lead indicate utilization of this antioxidant, either to scavenge oxyradical or act in combination with other enzymes. The acetylcholinesterase activity was found to be decreased during metal exposures. The results suggest that heavy metal does alter the active oxygen metabolism by modulating antioxidant enzyme activities, which can be used as biomarker to detect sublethal effects of pollution.